Precision Medicine for Frontotemporal Dementia - Liu, Mu-N; Lau, Chi-Ieong; Lin, Ching-Po (Frontiers in Psychiatry, 2019)
Frontotemporal dementia (FTD) is a common young-onset dementia presenting with heterogeneous and distinct syndromes. It is characterized by progressive deficits in behavior, language, and executive function. The disease may exhibit similar characteristics to many psychiatric disorders owing to its prominent behavioral features. The concept of precision medicine has recently emerged, and it involves neurodegenerative disease treatment that is personalized to match an individual’s specific pattern of neuroimaging, neuropathology, and genetic variability. In this paper, the pathophysiology underlying FTD, which is characterized by the selective degeneration of the frontal and temporal cortices, is reviewed. We also discuss recent advancements in FTD research from the perspectives of clinical, imaging, molecular characterizations and treatment. This review focuses on the approach of precision medicine to manage the clinical and biological complexities of FTD.